ANALISIS TINGKAT PEMAHAMAN PEMANGKU KEPENTINGAN TERKAIT PENERAPAN KONSEP GREEN ROAD DI KABUPATEN SORONG - Florida M. Turot (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The construction industry is a major contributor to pollution, resource depletion, waste, global warming, and climate change. The annual rate of road development has risen. In the process of creating a new road, emissions result from the manufacture of materials (asphalt, aggregate, asphalt mixture, and asphalt emulsion), the transportation of resources, the construction process, and the transportation of garbage. Throughout the life cycle of a project, the construction industry has adopted the notion of sustainability in order to minimize negative environmental impacts and improve social and economic well-being. Implementing a sustainable road is one of the measures taken to actualize the sustainability concept (green road). The aim of this study was to assess understanding of sustainable highways among stakeholders, including owners, contractors, planners, and academics/experts. The analysis in this study was carried out quantitatively and descriptively by using literature studies, RII techniques, and statistical tests. The results showed that the understanding of contractors and academics about the category of construction implementation activities and the category of pavement technology was still limited, while the understanding of consultants and owners about the green road category was quite comprehensive. Stakeholders have very diverse levels of knowledge in the category of construction implementation activities.